2022
DOI: 10.1186/s13098-022-00965-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the smartphone app DiaCert on health related quality of life in patients with type 2 diabetes: results from a randomized controlled trial

Abstract: Background Type 2 diabetes mellitus is associated with an increased risk of impaired quality of life. Improving health related quality of life (HRQoL) is therefore an important goal in the multimodal management of diabetes. The aim of this study was to evaluate whether the use of the smartphone app DiaCert, that encourage physical activity by promoting daily steps, also impacts HRQoL in patients with type 2 diabetes. Methods In this randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…In our modern intelligent era, mobile phones play a key role in everyday life, integrating functions such as communication, entertainment, education, and work [1][2][3]. Studies have indicated that the number of Chinese netizens is growing, with 99.8% of them using mobile phones to access the Internet [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our modern intelligent era, mobile phones play a key role in everyday life, integrating functions such as communication, entertainment, education, and work [1][2][3]. Studies have indicated that the number of Chinese netizens is growing, with 99.8% of them using mobile phones to access the Internet [4].…”
Section: Introductionmentioning
confidence: 99%